The Relevance of Credibility Excess in a Proportional View of Epistemic Injustice: Differential Epistemic Authority and the Social Imaginary - Medina, José (Social Epistemology, 2011)
This paper defends a contextualist approach to epistemic injustice according to which instances of such injustice should be looked at as temporally extended phenomena (having developmental and historical trajectories) and socially extended phenomena (being rooted in patterns of social relations). Within this contextualist framework, credibility excesses appear as a form of undeserved epistemic privilege that is crucially relevant for matters of testimonial justice. While drawing on Miranda Fricker's proportional view of epistemic justice, I take issue with its lack of attention to the role that credibility excesses play in testimonial injustices. I depart from Fricker's view of the relation between credibility excesses and credibility deficits, and I offer an alternative account of the contributions that undeserved epistemic privileges make to epistemic injustices. Then, through the detailed analysis of To kill a mockingbird, I elucidate the crucial role played by the social imaginary in creating and sustaining epistemic injustices, developing an analysis of the kind of social blindness produced by an oppressive social imaginary that establishes unjust patterns of credibility excesses and deficits.
Keywords: approches et analyses; cours; cycles supérieurs; discipline; droit; fem9000; histoire et politique; injustices épistémiques; inégalités; justice sociale; philosophie; privilèges; privilèges de crédibilité; science politique et droit; sciences humaines; systèmes d'oppressions; thématiques; éthique

The Routledge handbook of epistemic injustice - Kidd, Ian James; Medina, José; Pohlhaus, Gaile M. (Routledge handbooks in philosophy, 2017)
In the era of information and communication, issues of misinformation and miscommunication are more pressing than ever. Epistemic injustice--one of the most important and ground-breaking subjects to have emerged in philosophy in recent years--refers to those forms of unfair treatment that relate to issues of knowledge, understanding, and participation in communicative practices. The Routledge Handbook of Epistemic Injustice is an outstanding reference source to the key topics, problems, and debates in this exciting subject. The first collection of its kind, it comprises over thirty chapters by a team of international contributors, divided into five parts: Core Concepts; Liberatory Epistemologies and Axes of Oppression; Schools of Thought and Subfields within Epistemology; Socio-political, Ethical, and Psychological Dimensions of Knowing; Case Studies of Epistemic Injustice. As well as fundamental topics such as testimonial and hermeneutic injustice and epistemic trust the Handbook includes chapters on important issues such as social and virtue epistemology, objectivity and objectification, implicit bias, and gender and race. Also included are chapters on areas in applied ethics and philosophy, such as law, education, and healthcare. The Routledge Handbook of Epistemic Injustice is essential reading for students and researchers in ethics, epistemology, political philosophy, feminist theory, and philosophy of race. It will also be very useful for those in related fields, such as cultural studies, sociology, education, and law.
Keywords: approches et analyses; capacitisme; cours; cycles supérieurs; discipline; fem9000; hétérosexisme; injustices épistémiques; intersectionnalité; outils; ouvrages de références; philosophie; racisme; santé; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences; épistémologie; éthique; études critiques de la race; études critiques du handicap